Fundamentals of environmental management in companies - Alvarez Difurniao, Laura; Carmen María Pérez Mendoza, Carmen María; Valdes García, Cecilio; Alejandro Luis Cisnero Piñero, Alejandro Luis (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Environmental pollution is one of society’s current concerns, which is why companies have a significant responsibility to control their operations in order to mitigate this phenomenon. Proper waste management is an indispensable practice of corporate social responsibility and is a tool that increases the competitiveness of companies in a globalized environment, improving their image and reputation, efficiency in production processes and lower costs. The present study was carried out with the objective of describing the fundamentals of environmental management in companies. Various perspectives on environmental management strategies and practices can be implemented in companies, including the reduction of greenhouse gas emissions, responsible waste management, efficient use of natural resources, among other aspects. It also highlights the importance of collaboration between the private sector, government authorities and society in general to promote the adoption of sustainable practices in the meat industry.